2015
DOI: 10.4103/2394-5079.167376
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic curative effect of chicory extract and cisplatin against thioacetamide-induced hepatocellular carcinoma

Abstract: Aim: Hepatocellular carcinoma (HCC) is the dominant form of primary liver cancer and is histologically and etiologically distinct from other forms of primary liver cancer. The objective of this study was to elucidate the synergistic effect and the role of chicory extract [inulin (IN)] as a chemo-sensitizer for cisplatin (CIS) treatment of HCC. Methods: Five groups of rats were treated for 4 months. These groups consisted of the control group, a group receiving thioacetamide (TAA) (200 mg/kg b.w) in drinking wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
5
6
0
Order By: Relevance
“…sinusoids, due to loss of liver parenchyma. Previous studies on TAA-induced liver damage also showed prominent vascular alterations, such as sinusoidal dilatation and congestion and dilated and congested central vein (37,40) and are in accordance with the present study. Difference between Dsin values in the samples stained with Masson's trichrome showed higher values in the experimental, when compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…sinusoids, due to loss of liver parenchyma. Previous studies on TAA-induced liver damage also showed prominent vascular alterations, such as sinusoidal dilatation and congestion and dilated and congested central vein (37,40) and are in accordance with the present study. Difference between Dsin values in the samples stained with Masson's trichrome showed higher values in the experimental, when compared to the control group.…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, total bilirubin level was increase due to TAA‐induced oxidative stress and inflammation as conveyed by the current study. The results herein were in congruence with the preceding reports on TAA‐induced liver cell damage and cirrhosis (Hassan, Serag, Abdel‐Hamid, & Amr, ; Said, Said, Gameil, & Ammar, ; Shoeib et al, ). C. intybus linn supplementation improved liver cell synthetic and transport function, liver enzymes activities, and histopathological architecture, the condition that is in harmony with Hassan et al, .…”
Section: Discussionsupporting
confidence: 93%
“…Meanwhile, total bilirubin level was increase due to TAA-induced oxidative stress and inflammation as conveyed by the current study. The results herein were in congruence with the preceding reports on TAA-induced liver cell damage and cirrhosis(Hassan, Serag, Abdel- Hamid, & Amr, 2015;Said, Said, Gameil, & Ammar, 2013;Shoeib et al, 2018). C. intybus linn supplementation improved liver cell synthetic and transport function, liver enzymes activities, and histopathological architecture, the condition that is in harmony withHassan et al, 2015. Disturbed redox status as a result of oxidant/antioxidant imbalance causes oxidation of membrane lipid/proteins, DNA, structural and functional degeneration of cellular enzymes, and motivates proliferative/pro-inflammatory activity of HSCs nourishing the advance of liver fibrosis to cirrhosis…”
supporting
confidence: 93%
“…The anticancer effects of cisplatin, cyclophosphamide, and 5FU as chemotherapeutic drug used in the present study can easily related to the remarkable decrease of AFP as marker of HCC. This can be supported through related studies which found a decrease in AFP level after using these three drugs [[77], [78], [79], [80]].…”
Section: Discussionmentioning
confidence: 54%